2022
DOI: 10.20473/jmtt.v15i3.40294
|View full text |Cite
|
Sign up to set email alerts
|

Strategies to Improve Customer Experience: A Case of an Online Shopping Platform in Indonesia

Abstract: Background: As the e-commerce industry has been growing recently, it is crucial to examine the factors of customer experience towards online shopping platforms. In this study, researchers aim to examine the influence of website design, website security, and customer service towards customer experience that has led to the preference of online shopping platform in Malaysia. Purpose: The first objective of this study is to analyze the current situation of customer experience with the preferred online shoppi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 70 publications
(99 reference statements)
0
0
0
Order By: Relevance
“…Applied research is an investigation that is conducted by businesses or people with the intent of applying its findings to solve specific problems that are currently being experienced by the organization (Bougie & Sekaran, 2019). Therefore, to help achieve the three goals of this study, the researchers followed the three-step inquiry process as suggested by Wan Jusoh et al (2022) as follows:…”
Section: Methodsmentioning
confidence: 99%
“…Applied research is an investigation that is conducted by businesses or people with the intent of applying its findings to solve specific problems that are currently being experienced by the organization (Bougie & Sekaran, 2019). Therefore, to help achieve the three goals of this study, the researchers followed the three-step inquiry process as suggested by Wan Jusoh et al (2022) as follows:…”
Section: Methodsmentioning
confidence: 99%